Development of Website-Based Teaching Materials to Improve Historical Understanding in History Learning for Class X Students of SMA Negeri 1 Rangkat - Imory S, Amadhea Clarita; Ahmal, Ahmal; Asril, Asril (CV. Rayyan Dwi Bharata, 2024)
This research discusses the development of website-based teaching materials to improve understanding of history in history learning for class X students at SMA Negeri 1 Rangkat. The aim of this research is to determine the development of website-based teaching material design, determine the feasibility of developing website-based teaching materials, and understand history by using website-based teaching materials in history learning for class This research uses a Research and Development (RD) approach, namely an approach that produces and develops a physical product that has been tested for feasibility and effectiveness. Implementation of the RD approach using the PIE (Plan, Implement and Evaluate) development model. The results of this research show that the number of assessments given by media experts is 71 while the percentage obtained is 90% and the validation value is in the